Bacteremia After Orthodontic Miniscrew Insertion - Masood Feizbakhsh; Pedram Daneshkazemi; Sina Mobasherizade; Niloofar Fallah (Tehran University of Medical Sciences, 2022)
Objectives: Use of miniscrews has become very common in orthodontic treatment of patients. Following tissue manipulation during miniscrew placement, bacteremia may occur, which is important in patients susceptible to infective endocarditis. This study aimed to investigate the possibility of bacteremia following orthodontic miniscrew placement. Materials and Methods: The present quasi-experimental study was conducted on 30 orthodontic patients, including 11 males (36.7%) and 19 females (63.3%) with a mean age of 23.67±4.87 years, who required miniscrew placement in their treatment plan. Two blood samples were taken from the patients for aerobic and anaerobic cultures right before and 30-60 seconds after miniscrew placement. To investigate the presence of bacteremia, the blood samples were incubated in an automated blood culture machine for five days. The standard biological methods were used for the positive sample(s) to identify the type of bacteria. Data analysis was performed using the McNemar test. Results: The blood samples of 29 patients were negative for the bacteria before and after miniscrew placement. Blood sample of one patient was positive for aerobic and anaerobic bacteria after miniscrew placement. However, bacteremia was negative in the initial (preplacement) blood samples for both aerobes and anaerobes. Conclusion: Miniscrew placement in orthodontic patients was not associated with bacteremia.